Maintenance mud crab (scylla serrata) with different provision Of feed - Sugiani, Susi; Putra, Iskandar; ', Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted in March to May 2014 in the village of Dry Canang,XX Village, District Sicanang Belawan, Medan, North Sumatra Province. The methodused is the method of experiment by using RAL with 3 treatments and 3 replications thatis feeding trash fish (P1), feeding chicken intestine (P2), and feeding shellfish seashell(P3). Data were analyzed using ANOVA (P <0.05). Test materials were used as much as36 crabs were maintained with the battery system inside a cages measuring 60 x 35 x 17cm3. Cages divided into 4 sections by placing bamboo as a divider so that 1 basketcontains 4 crabs. The results showed that feeding trash fish produces growth weight106,52 g, daily growth rate 1,52%, growth in length 1,37 cm and a higher 1,13 cm andsurvival rate 100%.Keyword : mud crab, food, and growth